GENDER RESEARCHES IN THE STRUCTURE OF MODERN KNOWLEDGE - Shevchenko, L.Ya.; Alibek, T.K.; Nazarova, S.V. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The problem of equality between men and women from the perspective of the gender approach is examined in this article. The XXI century presents the principal new issues of current identification of women in the modern world, without the need for decisive advancement of humanity. This fundamental worldview shift is reflected in the concepts of gender science. Today, the "women's question" is the most important factor in the promotion of the status of women, identified opportunities and challenges for the modern society. By uncovering the social context of the "gender equality", the authors analyze the concept of the human civilization, the principles and criteria of the civil society, the priority of the public consent and peace, and brings forward the problem of women’s freedom.
Keywords: gender; knowledge; status; gender identity; status of woman; civil society